INCLUSIVE EDUCATION PROGRAM DEVELOPMENT: PROGRAM EVALUATION - Abdullah Abdullah; Billy Tunas; Muhammad Entang (UNIVERSITAS PAKUAN, 2021)
The objective of the research was to derive emphirical and analytical data. Additionally, to identify program implementation, substantif problems which affect context, input, process, and product (CIPP) in implementing inclusive education in elementary school. Evaluative Research Method with the CIPP Model approach developed by Stufflebeam (1967) was used. It was intended to evaluate the achievement of Program Implementation (Context, Input, Process, Product) to determine the success or failure of the program that has been implemented. The study was conducted at Education Office and Inclusive Education Provider Education Unit. Qualitative and quantitative data were collected using interviews, questionnaires, observations, documentation studies and focus group discussions, so that the data analyzed using the above methods succeeded in evaluating the components of the context, input, process, and product. Based on the results of the evaluation, the implementation of inclusive education in public elementary schools still needs the improvement in various aspects, especially in the components of Input, Process and Product, the results of this evaluation can be used as a reference for improvement in these components.